Conceptual foundations of classes with the disciples of special medical group in secondary schools - Vaskov, Y. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: study and scientific rationale for new approaches to the organization of educational work with students of special medical group in secondary schools. Material : analyzed 15 scientific sources regarding the approaches of different authors to develop educational programs for students of special medical group. Results : focuses on the outstanding issues in a substantive, logistical and human aspects. Found that the selection of the content of educational material for special medical groups is an empirical question. Selection is carried out by copying the existing curriculum of physical culture for healthy children with an indication of the load reduction and exemption of complex elements. Established a complete absence of evaluation of educational achievements of pupils. Based on modern approaches to teaching students based on biomedical and didactic aspects: Leading defined function of each stage of training, fleshed main goals and objectives of the educational process, substantiated various kinds of sports activity, taking into account the diagnosis of diseases and the needs of students of different ages and gender. Conclusions : the main controversy in the decision of the designated problem. Substantiated leading features of each stage of training in special medical groups. A system of assessment of students’ achievements.